we have
f(x)=4x^2+8x+1
Complete the square
step 1
Factor the leading coefficient 4
f(x)=4(x^2+2x)+1
step 2
f(x)=4(x^2+2x+1-1)+1
f(x)=4(x^2+2x+1)+1-4
f(x)=4(x^2+2x+1)-3
step 3
Rewrite as perfect square
f(x)=4(x+1)^2-3
step 4
Determine the solutions
equate the function f(x) to zero
4(x+1)^2-3=0
4(x+1)^2=3
(x+1)^2=3/4
square root both sides
![\begin{gathered} x+1=\pm\frac{\sqrt[]{3}}{2} \\ \\ x=-1\pm\frac{\sqrt[]{3}}{2} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/x3a1vp3oqtrkfg4yaozrhvhljwqxpx5i5t.png)
step 2
we have
f(x)=4(x^2+2x)+1
the number 2 divided by 2 is 1
so
add and subtract 1 not change the equation
f(x)=4(x^2+2x+1-1)+1
Apply the distributive property to -1
f(x)=4(x^2+2x+1)+4(-1)+1
f(x)=4(x^2+2x+1)-4+1
f(x)=4(x^2+2x+1)-3